Study of echocardiography in thalassemia (major/intermedia) patients at tertiary care center - B K, Usha; S, Stalin; T, Ravi Chandran; S, Gnanasambandam (Indian Journal of Child Health, 2018)
Objective: The objective of this study is to study the cardiovascular complications and to establish the role of echocardiography (ECHO) screening in beta thalassemia major (TM) and intermedia patients, aged 2–12 years, receiving one or more transfusions per month for 2 or more years. Methods: A cross-sectional study was done at tertiary care center from June 2015 to November 2015. Hemoglobin, serum ferritin, and 2D ECHO were done before the blood transfusion. Results: Male preponderance was seen with a ratio of 1.7:1. 87% (n=47) had TM and remaining had thalassemia intermedia (TI). Serum ferritin in TM was >1000 ng/ml in 80.9% (n=38) of cases and